Product and process innovations in a horizontally differentiated product market - Pia Weiss (Universität zu Köln, Institut für Wirtschaftspolitik (iwp), 2001)
For a market of horizontal product differentiation, the paper examines the effects of the level of competition on the firm's decision between a product and process innovation. When firms have to choose between the two types of innovation, it is demonstrated that both firms undertake the product innovation when the competition is intense. For intermediate levels of competition, the firms choose different investment projects, and for less intense competition, the firms pursue cost-reducing innovations. When firms may undertake both innovations, they decide to undertake a mixture of the innovations depending on the innovation cost structure. Again, the firms are willing to incur higher costs into product innovations, when the competition is initially intense.
Keywords: L13; 330; Product innovation; Process innovation; Horizontal product differentiation; Innovation; Investition; Produktdifferenzierung; Wettbewerb; Duopol; Theorie